ANALISIS (K3) PEKERJA MEBEL DI RUANG MESIN 1 DAN 2 MENGGUNAKAN (FTA) DAN (JSA) (Studi Kasus : CV.Kalingga Keling Jati) - Alam Akbar Al Fattah; Adung Jati Nugroho (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
CV Kalinga Keling Jati, furniture export company one of this industry. Identify control the potential work accidents in engine rooms 1 and 2 of CV Kalinga Keling Jati using the (FTA) and (JSA) methods. Work accident data from 2021 to 2023 shows a significant difference of accidents. in engine room 1 (48 cases) and engine room 2 (28 cases). Based on the risk evaluation, 16 work accidents were classified into small, medium, large risks, with six main events having the highest risk. The results of the analysis are the basis for developing recommendations for hazard control through the JSA Worksheet, including implementing routine training, using personal protective equipment (PPE), and better work scheduling. The benefit of this research is to increase awareness and work safety at CV Kalinga Keling Jati